Bridging the Islamic concept of parahuman force in managing the patient with mental health disorders - Wan Sulaiman, Wan Mohd. Azizi; Che Mohamad, Che Anuar; Mat Zain, Nora (2016)
According to Islamic belief, jinn are real creatures that form a world other than that of mankind, capable of causing physical and mental harm to human beings including possession. The beliefs that an individual has been entered by an alien spirit or other parahuman force, which then controls the person or alters that person’s actions and identity. This is often leads to underreported and undiagnosed because of the fear of misunderstanding by mental health professionals and community censure. Misunderstanding and wrongly informed the adverse effects of antipsychotic drugs make the situations worsened. Untreated mental illness can lead to serious personal and social consequences, including suicide. On the other hand, in our community, significant numbers of mental health patients seek the Islamic Medical Therapy using Ruqya Syari’yyah (RS) as their main treatment. In addition, the recent implementation of Traditional and Complementary Medicine Act 2016 has recognised the contribution of Islamic Medical Therapy using as part of complementary treatment. This review paper is hope to bridge and recognised the contribution of both discipline in treating mental health patients.